Pengaruh Cat pada Atap Galvalum untuk Mereduksi Suhu Bangunan Menuju Arsitektur Ramah Lingkungan - Sigit Ristanto; Yunita Dwi Saputri Ome; Ernawati Saptaningrum; Slamet Supriyadi; Bayu Arie Wibawa (Universitas Sebelas Maret Surakarta, 2025)
The issue of increasing temperature in buildings is a concern, especially in areas with high sun exposure. One factor affecting indoor temperature is the type and surface treatment of the roof. This study examines the effectiveness of paint in reducing the surface temperature of galvalume. The paint variables studied were type and colour. The experiment used an LM35 temperature sensor controlled by Arduino Uno. The roof without paint had the highest temperature increase with a gradient of 0.0276, while the roof with white B paint had the smallest gradient of 0.0086, showing its effectiveness in reducing heat absorption. The temperature difference between the upper and lower surfaces of the roof without paint is 7.6°C to 17.7°C, while with white B paint, it is only 2.6°C to 5.9°C. This indicates that reflective paint, especially white, enhances energy efficiency.